Understanding the world through the affordances of drama: early career teacher perspectives. Issue 1 (2nd January 2019) - Grove O'Grady, Alison Louise
ABSTRACT: This article contemplates the way five early career drama teachers in NSW speak and write about what they consider, the special characteristics and attributions of drama to facilitate learning in order for students to make sense of a complex world. These particular teachers reflect on their passionate individual beliefs in the affordances of drama to provision students with tools to mediate a changing world and that teaching drama permits them to create the conditions for students to challenge popular or dominant notions. These drama teachers believe that good drama teaching also allows meaningful learning to occur for students from a range of abilities including, physical ability. These teachers unanimously argue that teaching drama has corroborated their ideological positions and cemented their belief that drama is a critical tool for transforming learning in ways that promotes student voice and agency.